Obowiązek ochrony życia dzieci i młodzieży jako konstytucyjny imperatyw państwa. Analiza problemu samobójstw nieletnich w świetle art. 38 Konstytucji RP - Czarnek, Przemysław (PRAWO i WIĘŹ, 2026)
This paper examines the constitutional obligation to protect life, arising from Article 38 of the Constitution of the Republic of Poland, in the context of the growing phenomenon of suicide among children and adolescents. The aim of the study is to define the scope of the state's constitutional responsibility, identify systemic barriers to preventing juvenile suicide, and present de lege ferenda and de lege lata recommendations. The paper incorporates a dogmatic, legal, and comparative analysis, thus highlighting the need for urgent legislative and institutional action to effectively protect the lives of our youngest citizens.